2017
DOI: 10.1504/ijicbm.2017.10000829
|View full text |Cite
|
Sign up to set email alerts
|

Quality issues affecting organisational performance: a review of Indian technical education

Abstract: Indian technical education, in the recent past, experienced an exponential growth causing degradation in the employability of engineering graduates. This affected the business performance of many private technical institutions in India which are now on the brink of extinction. Low employability of engineering graduates may render them jobless and may convert the so called India's demographic dividend into the demographic disaster. Therefore, it is imperative to analyse the quality issues affecting the performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…All India Council for Technical Education, New Delhi, an apex body for governing technical education, indicated that approximately 45% of seats remained vacant in the 2019-2020 academic year, which was earlier noticed to be 38% in 2012-2013. Most of the studies have verified that this situation is due to problems pertaining to awareness, attraction, recognition of needs and service offers ( Kamokoty et al, 2015 ; Upadhayay & Vrat, 2017 )…”
Section: Introductionmentioning
confidence: 99%
“…All India Council for Technical Education, New Delhi, an apex body for governing technical education, indicated that approximately 45% of seats remained vacant in the 2019-2020 academic year, which was earlier noticed to be 38% in 2012-2013. Most of the studies have verified that this situation is due to problems pertaining to awareness, attraction, recognition of needs and service offers ( Kamokoty et al, 2015 ; Upadhayay & Vrat, 2017 )…”
Section: Introductionmentioning
confidence: 99%
“…Quality of education is a prime, discriminating, and prominent characteristic of an engineering institute consigned to stay ahead in competition and to make a place in the minds of stakeholders. Several studies (Pandi et al, 2014) (Upadhayay & Vrat, 2017) (Sakthivel & Raju, 2006a) (Jain et al, 2013) have emphasized the importance of the quality aspect, which is responsible for the qualitative and holistic development of engineering students and important in making institute choice decisions (Paulsen, 1990c) (Kallio, 1995) (Mourad, 2011) (McCarthy et al, 2012. From India's perspective, several items, such as academic standards, industry linkages, campus placements, research and consultancy, accreditation and financial standing, contribute to the quality of education, as mentioned by (Mahajan et al, 2014).…”
Section: Quality Educationmentioning
confidence: 99%
“…Dashboard of All India Council for Technical Education, New Delhi displayed that approximately 45% of seats remained vacant in the 2019-2020 academic year, which was 38% in 2012-2013. The quality of engineering education in the Indian setting appears to be the lowest compared to that in other developing countries (Loyalka et al, 2014) due to the problems pertaining to awareness, attraction, inclusion of diversity and service quality (Kamokoty et al, 2015;Lakal et al, 2018;Upadhayay and Vrat, 2017). Despite the fact that demand for engineers remains relatively high, few students are willing to pursue engineering education.…”
Section: Introductionmentioning
confidence: 99%
“…Quality of education is a prime, discriminating, and prominent characteristic of an engineering institute consigned to stay ahead in competition and to make a place in the minds of stakeholders. Several studies (Pandi et al, 2014) (Upadhayay & Vrat, 2017) (Sakthivel & Raju, 2006a) (Jain et al, 2013) have emphasized the importance of the quality aspect, which is responsible for the qualitative and holistic development of engineering students and important in making institute choice decisions (Paulsen, 1990c) (Kallio, 1995) (Mourad, 2011) (McCarthy et al, 2012. From India's perspective, several items, such as academic standards, industry linkages, campus placements, research and consultancy, accreditation and nancial standing, contribute to the quality of education, as mentioned by (Mahajan et al, 2014).…”
Section: Quality Educationmentioning
confidence: 99%